PP01 What are the different types of alcohol consumption among the youth of society? A narrative synthesis. (2nd September 2014) - Davoren, MP; Cronin, M; Perry, IJ; Demant, J; O'Connor, K
Abstract : Background: Hazardous alcohol consumption is a global phenomenon linked to numerous health and social problems. Consumption levels are significantly higher among younger age groups and patterns of consumption vary significantly among individuals. However, public health policy attempts a 'one size fits all approach' failing to consider opposing needs and types of consumption. The aim of the current study was to synthesise information from studies that presented types of alcohol consumption among a youth population. Methods: Literature eligible for inclusion in this review included qualitative and quantitative studies published in peer reviewed journals, investigating the different types of drinkers, among a young adult population [aged 12–24 years]. MEDLINE, PsychInfo and CINAHL were searched for relevant articles separately by qualitative and quantitative research from inception up until October 31 st 2013. Included papers were critically appraised. A narrative synthesis approach was employed based on guidance from the UK Economic and Social Research Council. Results: In total, 14 studies were eligible for inclusion: twelve quantitative, one qualitative and one mixed methods. Six classes of drinkers emerged from this typology. Abstainers reported no alcohol consumption. Light drinkers reported drinking small amounts of alcohol infrequently. In comparison social and hedonistic drinkers drank most in social situations and to have fun. Heavy and harmful consumers reported increased volume and frequency of consumption including binge drinking and harmful consequences. Discussion: Currently, policy makers are attempting to combat the high levels of harmful alcohol consumption among the youth of society. With individuals reporting different patterns of alcohol consumption, a variety of initiatives must be considered to tackle the issue. These range from harm minimisation such as minimum unit price for alcohol, taxation, reducing beverage sizes or tackling marketing policies to funding addiction services for recovery from alcohol addiction.